STRENGTHENING NARRATIVE WRITING SKILL THROUGH DIGITAL STORYTELLING - Nofitasari, Filda Dyah; Nuroh, Ermawati Zulikhatin; Megawati, Fika (Indonesian EFL Journal, 2024)
Writing is a common activity that is used by everyone. Such as writing reports, literary works, articles, books, comics, newspapers, and others. Writing is an active and productive language action. Language productive activities are activities to convey ideas, thoughts, or feelings by the narrator, in this case, the author, in writing activities, language structure This study uses pre-experimental quantitative research on a population of 40 students. sampling is a sampling technique in which the researcher selects several members of the population at random based on several criteria. Based on the results of this research, it can be concluded that the influence of simultaneous digital storytelling on narrative writing is 0.00 < 0.05 and the calculated F value is 71.070 > F table 3.01, so we might conclude that digital storytelling is accepted, which means there is a positive influence. simultaneous to narrative writing. This was also indicated by the pre-test and post-test carried out by class 8A MTS Plus Nabawi students. Which was marked by an increase in the average score of students 8A on the test carried out. This test is related to content, organization, and language, where in all these tests there is an increase in scores after the post-test is carried out